The Main Female Characters' Oppression in Girls Burn Brighter by Shobha Rao - Rizky, Wilma Afrilia (English Literature Study Program, 2023)
The perception of the women's inferiority in society has created significant issues in the form of oppression of women. Furthermore, literary works portrayed these issues to raise awareness because it has an important role as one of the means to address the issue of oppression against women. Shobha Rao's novel Girls Burn Brighter is a feminist literary work that highlights the oppression of women. This study aims to examine the oppression of main female characters as revealed in the novel through literary devices. This study used a sociological approach since the novel raise the social phenomena of female oppression which is examined through the perspective of feminist literary criticism. The researcher applies Iris Young's theory of oppression to explore the forms of oppression and Kimberly Crenshaw's theory of intersectionality to look out the factors of oppression experienced by main female characters. The results of this study found that the main female characters, namely Poornima and Savitha, experience oppression in the form of marginalization, exploitation, powerlessness, cultural imperialism, and violence. Their experiences of oppression manifest in the form of marginalization of job opportunity, sexual and labor exploitation, powerlessness to speak up, cultural imperialism of the dowry system, and physical and sexual violence. These forms of oppression are influenced by intersecting factors such as gender, social class, political power, skin color, and dominant culture. Keywords: oppression, intersectionality, feminist literary criticism